Inisiasi Kampanye Remaja Puteri Bebas Anemia (IKRAR BASMIA) di Kecamatan Tanambulawa Kabupaten Sigi: Initiation of Anemia Free Young Girls Campaign (IKRAR BASMIA) in Tanambulawa District, Sigi Regency - Taqwin, Taqwin; Linda, Linda; Suryani, Lili; Pani, Widya; Hasnawati, Hasnawati; Narmin, Narmin; Lisnawati, Lisnawati; Nasrul, Nasrul (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The campaign for anemia-free adolescent girls has never been carried out in the working area of the Tanambulawa Health Center. The purpose of community service is to initiate an anemia-free adolescent campaign (IKRAR BASMIA) in the work area of the Tanambulawa Health Center. The method of service involves providing training through focus group discussions and the installation of billboards about the BASMI Pledge. The implementation time will be March 13–24, 2023, at the South Sibalaya Village Hall, Tanambulawa District, Sigi Regency, Central Sulawesi. The participants were 11 teenage girls. Evaluation method through pretest and posttest questionnaires. The results of the service showed an average knowledge score of 4.18 for pretest participants and 5.73 for posttest participants. The installation of BASMIA Pledge billboards has been carried out in a strategic place in Sibalaya Village. The conclusion of the dedication was an increase in the average value of participants' knowledge from pretest to posttest. The installation of BASMIA Pledge billboards has been carried out in Tanambulawa Regency.